Reorienting the East : Jewish Travelers to the Medieval Muslim World - Jacobs, Martin, 1963- (Book collections on Project MUSE., 2014)
The first comprehensive investigation of premodern Jewish travel writing about the Islamic world, Reorienting the East examines Hebrew and Judeo-Arabic travel accounts from the mid-twelfth to the early sixteenth centuries that subvert, or reorient a decidedly Christian vision of the region and reflect changing Jewish self-perceptions.